Implementasi Metode Iqra’ Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Anak Usia Dini - Mursal Aziz; Dedi Sahputra Napitipulu; Asmidar Sianipar (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2024)
This study aims to analyze the application of the Iqro method in improving the ability to read the Qur'an in Early Childhood. This study used the Classroom Action Research (PTK) method. The results of this study show that the use of the Iqra method in an effort to improve the ability to read the Qur'an in PAUD Ummi, Teluk Binjai Village, Kualuh Hilir District, North Labuhanbatu Regency can be said to be very successful and have a significant impact. Where based on preliminary studies it was found that the majority of students have not been able to read the Qur'an. But after using the Iqro method, it was found that in the first cycle there were 4 people or 23.52% of the current category, 5 people or 29.41% of the medium category, and 8 people or 47.05% of the less category. While in the second cycle there were 11 people or 64.70% of the current category, 4 people or 23.52% of the medium category, and 2 people or 11.76% of the less category.